Semantic Analysis On The Use Of Hijab And Jilbab Word Based On Qur’anic Perspective - Andi Miswar (Jurnal Adabiyah: Humanities and Islamic Studies, 2019)
The article explorer the difference of the word hijab and veil in the Qur'an verses through semantic analysis. The use of the word hijab for veil clothing is popular and both words are sometimes interpreted in the same meaning without defining the slightest difference with connotation on clothing. Moreover, through a qualitative descriptive analysis process with a lexical-semantic analysis method that used an interpretation variety technique through maudhui method with a research object in al-Qur’an verses which related to the use of the word hijab and veil, it revealed that the two words hijab and veil have a different meaning. The results revealed that the word hijab shows the meaning of covering, boundary or wall, as an intermediary which limited between men and women or between objects with another object, which aimed to prevent adversity (assimilation) with the opposite sex, and the use of the word hijab has been mentioned in the Qur'an eight times scattered in eight surah, and there is no definite editorial found that the meaning of clothes attached to a woman's body. While the use of the veil word is mentioned twice and found in two surahs, which indicated the meaning of clothing that covers the entire body of a woman, even though some people argued except covering the face and palms. Thus, this article is important because it discussed the different meanings of the use of both words in al-Qur'an through Semantic analysis, and it contributed to provide the real meaning and straighten the misunderstanding about those words both terms and understanding the related verses. Artikel ini membahas perbedaan penggunaan kata hijab dan jilbab dalam ayat-ayat al-Qur’an dengan analisis semantik . Penggunaan kata hijab untuk pakaian jilbab menjadi populer dan  kedua kata tersebut  terkadang diartikan sama tanpa memiliki perbedaan sedikitpun dengan berkonotasi pada pakaian. Namun setelah melalui proses analisis secara deskriptif kualitatif dengan metode analisis semantik leksikal yang menggunakan pendekatan berbagai teknik interpretasi dalam  metode maudhui dengan obyek penelitiannya pada ayat-ayat al-Qur’an yang berkenaan dengan penggunaan kata hijab dan jilbab, ternyata kedua kata tersebut memiliki makna yang berbeda. Hasil penelitian menunjukkan bahwa kata hijab menunjukkan makna tabir, batas atau dinding, sebagai perantara yang membatasi antara pria dan wanita atau antara satu benda dengan benda lainnya, yang bertujuan untuk mencegah ikhtilat (pembauran) dengan lawan jenis, dan dari seluruh penggunaan kata hijab yang disebut dalam al-Qur’an sebanyak delapan kali yang tersebar pada delapan surah,  tidak ditemukan secara pasti redaksi yang menunjukkan makna pakaian yang melekat pada tubuh wanita. Sementara penggunaan kata jilbab yang disebut sebanyak dua kali yang terdapat pada dua surah, keduanya menunjukkan makna pakaian yang menutupi seluruh anggota tubuh wanita, meskipun ada yang memahami kecuali muka dan telapak tangan. Dengan demikian, artikel ini menjadi penting karena mengurai  perbedaan makna penggunaan kedua kata tersebut dengan analisis semantik Qur’ani, dan berkontribusi untuk memberikan pemahaman sehingga tidak terjadi kekeliruan, baik dalam penggunaan term tersebut maupun dalam memahami ayat yang terkait.